Canada and the Great War : Western Front Association papers - Busch, Briton Cooper (McGill-Queen's University Press, 2003)
Canada and the Great War explores the military and socio-cultural history of World War I, adding new dimensions not only to the history of Canadas role in the war but to the wars role in shaping Canada.